Ecological, behavioral, and phylogenetic influences on the evolution of dorsal color pattern in geckos. (4th February 2020) - Allen, William L.; Moreno, Nickolas; Gamble, Tony; Chiari, Ylenia
Abstract: The dorsal surfaces of many taxonomic groups often feature repetitive pattern elements consisting of stripes, spots, or bands. Here, we investigate how distinct categories of camouflage pattern work by relating them to ecological and behavioral traits in 439 species of gecko. We use phylogenetic comparative methods to test outstanding hypotheses based on camouflage theory and research in other taxa. We found that bands are associated with nocturnal activity, suggesting bands provide effective camouflage for motionless geckos resting in refugia during the day. A predicted association between stripes and diurnal activity was not supported, suggesting that stripes do not work via dazzle camouflage mechanisms in geckos. This, along with a lack of support for our prediction that plain patterning should be associated with open habitats, suggests that similar camouflage patterns do not work in consistent ways across taxa. We also found that plain and striped lineages frequently switched between using open or closed habitats, whereas spotted lineages rarely transitioned. This suggests that pattern categories differ in how specialized or generalized their camouflage is. This result has ramifications for theory on how camouflage compromises to background heterogeneity and how camouflage pattern might influence evolutionary trajectories.